Type VI choledochal cyst - An emerging rare entity (11th pediatric case of type VI) with a review of literature - A Sushma; Rajeev Redkar; Rahul Deo Sharma; Surendra Singh; Sonia Thakur; Asha Mary George (Wolters Kluwer Medknow Publications, 2023)
Choledochal cysts (CCs) are abnormal dilatations of the biliary system. Usually, CCs are classified into five types. The sixth type (Type VI) is an emerging and rare type, reported the first case in 1991. We report this rare CC, Type VI seen in our experience for the first time. We have also reviewed the literature; only 26 cases of Type VI were found, including adults and children, ever since the first case has been reported in 1991. To the best of our knowledge, this is the 11th pediatric case report of a Type VI choledochal cyst.